Urgensi Manajemen Peningkatan Mutu Berbasis Sekolah Di Lembaga Pendidikan Islam - Mubaidi Sulaeman (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
MBS is born with several different names: school-based governance, school self-management, and even school-based management. These terms do have an understanding with a slightly different emphasis. However, the names have the same spirit, ie the school is expected to become more autonomous in the implementation of school management, especially in the use of 3M its man, money, and material. The main objective is to develop school policy procedures, solve common problems, and utilize all potential individuals who are members of the team. So the school can only print people who are intelligent and emotionally high, but also can prepare the development workers. Therefore the Islamic education institution is very necessary to apply MPMBS to make the school as an integral part of society, it is not a separate institution of society, the right to life and the survival of the school depends on the community, the school is a social institution that serves to serve members of the community in education, school and community progress are mutually exclusive, both need each other.